INCLUSIVE ART EDUCATION: INTERNATIONAL EXPERIENCES AND IMPLEMENTATION CHALLENGES IN UZBEKISTAN - Ergasheva Dilnoza Raximjonovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores inclusive art education, analyzing international experiences and examining the challenges of implementing inclusive practices in Uzbekistan. The study highlights pedagogical strategies, curriculum adaptations, and classroom techniques that facilitate the participation of students with diverse abilities. Examples from countries such as Finland, the United States, Germany, and South Korea are discussed, emphasizing inclusive teaching methods, assistive technologies, and collaborative learning approaches. The article also considers how these practices can be adapted to the Uzbek educational context, balancing international best practices with national educational policies and cultural traditions. Findings suggest that inclusive art education can enhance creativity, engagement, and social development for all students when effectively implemented.